Brawl in Perspective of Positive Crime and Islamic Crime - Ramadi, Bagus; Sahputra, Asep (Universitas Islam Negeri Sumatera Utara, 2022)
General crime is defined as an act that violates legal regulations for which a person can be punished. Crime will exist if someone violates the law, either directly or indirectly, or in the form of negligence which can result in punishment. According to Article 28 G paragraph (1) of the 1945 Constitution, criminal acts violate a person's human right to feel safe. The author will review the problems that arise, namely: how to resolve brawls from the perspective of positive crime and Islamic crime. This research uses a normative juridical approach. The approach taken is based on primary legal sources and considers theories, concepts, legal principles and legal regulations that are relevant to this study. This approach is also called a bibliographic approach by studying books, statutory regulations and other documents related to the research. Because most brawlers themselves are children or teenagers whose age is not yet legally competent according to criminal law. The imposition of criminal penalties for children or teenagers is regulated in Article 59 paragraph (2) letter b of Law Number 35 of 2014 concerning Child Protection, that a child who is in conflict with the law is given special legal protection, namely: a) Humane treatment by paying attention to needs. according to his age. b) Separation from adults. c) Providing effective legal and other assistance. d) Implementation of recreational activities. e) Freedom from torture, punishment or other cruel, inhumane and degrading treatment. f) Avoidance of the death penalty and/or life imprisonment. g) Avoidance of arrest, detention or imprisonment, except as a last resort and for the shortest time. h) Providing justice before a juvenile court that is objective, impartial and in a trial that is closed to the public. i) Avoidance of publication of his identity. j) Providing assistance from parents/guardians and people trusted by the child. k) Providing social advocacy. l) Giving personal life. m) Providing accessibility, especially for children with disabilities. n) Providing education. o) Provision of health services. p) Granting other rights in accordance with statutory provisions. Public crimes are defined as acts that violate legal regulations so that a person can be punished.